2021
DOI: 10.1136/bmjopen-2020-046130
|View full text |Cite
|
Sign up to set email alerts
|

Potential solutions for screening, triage, and severity scoring of suspected COVID-19 positive patients in low-resource settings: a scoping review

Abstract: ObjectivesPurposefully designed and validated screening, triage, and severity scoring tools are needed to reduce mortality of COVID-19 in low-resource settings (LRS). This review aimed to identify currently proposed and/or implemented methods of screening, triaging, and severity scoring of patients with suspected COVID-19 on initial presentation to the healthcare system and to evaluate the utility of these tools in LRS.DesignA scoping review was conducted to identify studies describing acute screening, triage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The models developed in this study establish how one can differentiate COVID-19 from influenza, albeit only if a computerized decision aid could interview the patient and calculate the probability of a likely infection. Such method of assessment and triage would be helpful if access to at-home COVID-19 tests were limited, as experienced in the United States for some time [16], and as it continues to be limited in many low-and moderate-income countries [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The models developed in this study establish how one can differentiate COVID-19 from influenza, albeit only if a computerized decision aid could interview the patient and calculate the probability of a likely infection. Such method of assessment and triage would be helpful if access to at-home COVID-19 tests were limited, as experienced in the United States for some time [16], and as it continues to be limited in many low-and moderate-income countries [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…For application in low-and middle-income settings, as rapid COVID tests are not available, triage tools must be applied to patients with suspected COVID and must use easily obtainable clinical factors, as opposed to laboratory and other investigations. 1,4 Prognostic research to date has largely been conducted in inpatient and highincome settings on patients with confirmed COVID-19. [4][5][6] Acuity scores, including the UK Royal College of Physicians National Early Warning Score, version 2 (NEWS2), COVID specific Pandemic Respiratory Infection Emergency System Triage (PRIEST) score and Quick COVID-19 Severity Index have shown good prediction of adverse outcomes and been suggested as a way to risk-stratify patients with suspected COVID-19 in the Emergency Department.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted in the United Arab Emirates (UAE), which hosts over 200 nationalities, and about 88.5% of the population are expatriates and immigrants from other Middle Eastern and South Asian countries ( 9 ). Secondly, a recent critical appraisal and systemic analysis revealed that most published predictive models have significant selection bias and poorly defined predictors and outcomes, as well as lacking calibration and validation, making their generalizability and implementation across different settings and populations questionable ( 10 , 11 ). Our predictive models were developed in accordance with the TRIPOD statement's recommendations with complete data on disease progression and clearly defined final outcomes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%